Intensive care unit nurses' perceptions and practices regarding clinical alarms: A descriptive study - Lei Wang; Wei He; Yulu Chen; Qiuping Wu; Xin Du; Qin Li; Caiping Song (Wiley, 2023)
Abstract Aim To describe the frequencies of physiologic monitor clinical alarms and to investigate nurses' perceptions and practices regarding clinical alarms in ICUs. Design A descriptive study. Methods A 24‐h continuous nonparticipant observation study was conducted in ICU. Observers observed and recorded the occurrence time, detail information when electrocardiogram monitor alarms triggered. And a cross‐sectional study was conducted among ICU nurses by convenience sampling, using the general information questionnaire and the Chinese version of clinical alarms survey questionnaire for medical devices. Data analysis was performed using SPSS 23. Results A total of 13,829 physiologic monitor clinical alarms were recorded in 14‐day observation and 1191 ICU nurses responded to the survey. Most nurses agreed or strongly agreed the sensitivity to alarms and responded quickly (81.28%), smart alarm systems (74.56%), alarm notification systems (72.04%) and set up alarm administrators (59.45%) were useful to improve alarm management, while frequent nuisance alarms disrupted patients care (62.47%) and reduced nurses' trust in alarms (49.03%), environmental noise interfered with nurses' recognition of the alarms (49.12%) and not everyone received education of alarm systems (64.65%). Conclusions Physiological monitor alarms occur frequently in ICU, and it is necessary to formulate or further optimize alarm management measures. It is recommended to use smart medical devices and alarm notification systems, formulate and implement standardized alarm management policies and norms, and strengthen alarm management education and training, so as to improve the nursing quality and patient safety. Patient or Public Contribution The patients in the observation study included all patients admitted to the ICU during the observation period. The nurses in the survey study were conveniently selected through an online survey.